Enhanced densification and mechanical properties of β-boron by in-situ formed boron-rich oxide. (10th February 2022) - Zhang, Haibo; Örnek, Metin; Lahkar, Simanta; Song, Shuangxi; Wang, Xiaodong; Haber, Richard A.; Reddy, Kolan Madhav
Highlights: Fully dense β-boron was obtained at 1800 °C with 50 MPa for 5 min using spark plasma sintering. New boron-rich oxide (B96 O4 ) structure evolution was studied using advanced analytical TEM. Hardness of B96 O4 phase is 41 ± 2 GPa which is 10% higher than that of β-boron. In-situ formed boron-rich oxide contributes to densification and enhancing the properties of β-boron. Abstract: We report nearly full densification of polycrystalline rhombohedral beta (β)-boron without the addition of sintering aids via spark plasma sintering (SPS). The analytical aberration corrected transmission electron microscope observations have revealed in-situ growth of nanocrystalline boron-rich oxide precipitates that contain approximately 4 at.% of oxygen and beget the densification of β-boron. Further electron energy loss spectroscopy and diffraction analysis confirmed that the newly formed boron-rich oxide (nominally B96 O4 ) structure with B-O σ-bonding belongs to space group R 3 ¯ m . Depth sensitive nanoindentation showed boron-rich oxide phase has a hardness of about 41 ± 2 GPa, which is 10% higher than that of β-boron matrix. The estimated hardness and fracture toughness of β-boron were approximately 31 GPa and 2.2 MPa m 1/2, respectively, using Vickers microindentation, which falls in the range of those commercially used boron carbides. These results suggest that the enhanced densification and mechanical properties arise from the newly formed boron-rich oxide in β-boron during SPS experiments. Graphical abstract: Image, graphical abstract